Determinant factors in climbing ability: Influence of strength, anthropometry, and neuromuscular fatigue. Issue 10 (10th October 2015) - Laffaye, G.; Levernier, G.; Collin, J.‐M.
Abstract : The goal of this study was to (i) assess the physical and anthropometric differences between three levels of climbers and (ii) predict climbing ability by using a multiple regression model. The participants were divided into novice ( n  = 15), skilled ( n  = 16), and elite ( n  = 10) climbers. Anthropometric characteristics such as height, weight, percentage of body fat and muscle, bi‐acromial breath, arm span, and ape index were measured. General and specific strength were assessed through an arm jump test, a bench press test, and a hand and finger grip strength test in maximal and endurance conditions. All variables were combined into components via a principal component analysis (PCA) and the components used in a multiple regression analysis. The major finding of this study is that climbing ability is more related to specific rather than general strength. Only finger grip strength shows a higher level of initial strength between all samples while the arm jump test discriminates between climbers and non‐climbers. The PCA reveals three components, labeled as training, muscle, and anthropometry, which together explain 64.22% of the variance. The regression model indicates that trainable variables explained 46% of the total variance in climbing ability, whereas anthropometry and muscle characteristics explain fewer than 4%.